The Effect of Consumption Value on New Products Adoption: An Evidence of Smart Phones in Ho Chi Minh City Market, Viet Nam - Du Thi Chung (International Journal of Small and Medium Enterprises and Business Sustainability, 2020)
The purpose of this study is to investigate the role of consumption value in the purchase intention of new smart phones in emerging market as Viet Nam. This study draws on the calls that manufacturers should pay more attention to enhance consumer perceived value, hence increasing new product adoption rate. Regression analyses were employed to test the model and research hypotheses, using a data set of convenience samples surveyed from 430 smart phone users in Ho Chi Minh city, Viet Nam. The empirical findings indicate three consumption values that have positive impacts on the intention to purchase new smart phones, including functional value, social value and cognitive value. The research results are discussed and some implications for smart phone manufacturers and policy makers are proposed.